2010
DOI: 10.1002/cne.22279
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of pre‐ and postsynaptic sex differences in the nucleus accumbens

Abstract: The nucleus accumbens (NAc) plays a central role in motivation and reward. While there is ample evidence for sex differences in addiction-related behaviors, little is known about the neuroanatomical substrates that underlie these sexual dimorphisms. We investigated sex differences in synaptic connectivity of the NAc by evaluating pre- and postsynaptic measures in gonadally intact male and proestrous female rats. We used DiI labeling and confocal microscopy to measure dendritic spine density, spine head size, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
96
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(110 citation statements)
references
References 93 publications
(127 reference statements)
14
96
0
Order By: Relevance
“…The current findings suggest that AAS also enhance the effects of physiologic testosterone on Acb. In Acb, females have greater spine density than males (Forlano and Woolley, 2010; Wissman et al 2011), and vehicle-treated males have greater spine density than AAS-treated males (current study). Thus, higher testosterone corresponds to lower spine density in Acb.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…The current findings suggest that AAS also enhance the effects of physiologic testosterone on Acb. In Acb, females have greater spine density than males (Forlano and Woolley, 2010; Wissman et al 2011), and vehicle-treated males have greater spine density than AAS-treated males (current study). Thus, higher testosterone corresponds to lower spine density in Acb.…”
Section: Discussionsupporting
confidence: 47%
“…Although previous studies report higher Acb spine densities in male rats compared with vehicle-treated males in the present study, this likely reflects the different methods (DiI vs Golgi) used to visualize neuronal morphology. In particular, the DiI labeling used by Forlano and Woolley (2010) and Wissman et al (2011) yields higher spine densities than Golgi impregnation in pyramidal cells of CA1. (Woolley et al 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that sexually dimorphic responses are due to sex differences in gonadal hormones, monoaminergic levels, metabolic processes, or D1 receptor sensitivity (Sell et al 2000;Festa et al 2004;Nazarian et al 2004). More recently, a structural and functional basis for these behavioral differences has been identified in the NAc, where cocaine promotes greater induction of dendritic spine density and proportionally more large spines in both the core and shell in female compared with male rats (Forlano and Woolley 2010). Cocaine also promotes a larger increase in miniature excitatory postsynaptic current (EPSC) frequency, a functional correlate of increased spine density along with enhanced behavioral sensitization (Wissman et al 2011).…”
Section: Sex Differences and Structural Plasticitymentioning
confidence: 99%
“…Two parts of the accumbens nucleus are reported to be sexually dimorphic: core/shell gender differences have been outlined as more expressed in the core region (Forlano and Wooley, 2010).…”
Section: Discussionmentioning
confidence: 99%